Palliative care knowledge, information sources, and beliefs: Results of a national survey of adults in the USA. Issue 3 (June 2020) - Adjei Boakye, Eric; Mohammed, Kahee A.; Osazuwa-Peters, Nosayaba; Lee, Min Jee; Slomer, Lauren; Emuze, Damilola; Jenkins, Wiley D.
Abstract: Objective: Despite its established benefits, palliative care (PC) is not well known among patients and family/caregivers. From a nationally representative survey, we sought to assess the following associated with PC: knowledge, knowledge sources, and beliefs. Methods: Data were drawn from the Health Information National Trends Study (HINTS 5 Cycle 2), a cross-sectional, survey of non-institutionalized adults aged 18+ years in the USA. Data were weighted and assessed by proportional comparison and multivariable logistic regression. Results: A total of 3504 respondents were identified, and approximately 29% knew about PC. In the adjusted model, less PC knowledge was associated with: lower age (those aged <50), male gender, lower education (<high school graduation or high school graduate), and non-internet users. A little over half (55%) of respondents accessed healthcare providers first for PC information, and 80% considered providers the most trusted source of PC information. Most of the participants strongly/somewhat agreed that the goal of PC is to help friends and family cope with a patient's illness (90.6%), offer social and emotional support (93.4%), and manage pain and other physical symptoms (95.1%). Similarly, a majority (83.3%) strongly/somewhat agreed that it is a doctor's obligation to inform all patients with cancer about the option of PC. Significance of results: PC knowledge was generally low (1-in-3 respondents knew of PC), with significant differences according to age, gender, education, and internet use. These data provide a baseline from which PC education policies and interventions may be measured.